Responses of quail to dietary vitamin E and zinc picolinate at different environmental temperatures - Şahin, Kazım; Onderci, M.; Şahin, Nurhan.; Gulcu, F.; Yildiz, N.; Avci, M.; Küçük, Ömer (Elsevier, 2006)
The effects of Vitamin E (DL-alpha-tocopheryl acetate) and zinc picolinate (ZnPic(2)) supplementation on performance, carcass quality, serum malondialdehyde (MDA) as lipid peroxidation indicator, Vitamins C and E, zinc and cholesterol concentrations in the Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature were evaluated. Two hundred and seventy 10-day-old Japanese quails were randomly assigned to nine treatment groups, three replicates of 10 birds each in a 2 x 3 x 3 factorial arrangement of treatments. Birds were kept in a temperature-controlled room at either 22 degrees C (Thermo-neutral, TN) or 34 degrees C (Heat stress, HS) for 8 h/d (09.00 am-05.00 put and fed a basal (control) diet or the basal diet supplemented with either three levels of Vitamin E (0, 125 and 250 mg of DL-alpha-tocopheryl acetate/kg of diet) or three levels of zinc (0, 30 and 60 mg of zinc picolinate/kg of diet). Birds kept at high ambient temperature 34 degrees C consumed less feed intake and gained less weight (P < 0.001) compared with control temperature birds. A linear increase in feed intake (P < 0.01) and body weight (P < 0.01), and improvement in feed efficiency (P < 0.01) and carcass quality (P < 0.05) were found in Vitamin E and zinc-supplemented quail reared under heat stress conditions. The interaction between Vitamin E and zinc for final body weight change (P < 0.01) and feed intake (P < 0.05) was detected. Final body weight change and feed efficiency increased to a higher extent by increasing dietary Vitamin E when higher zinc levels were fed. Serum Vitamin C (P < 0.001), Vitamin E (P < 0.001) and zinc (P < 0.001) concentrations linearly increased, whereas MDA concentrations linearly decreased (P < 0.001) as dietary Vitamin E and ZnPic supplementation increased. Results of the present study conclude that a combination of dietary Vitamin E (250mg) and zinc picolinate supplementation (30 mg) may alleviate heat stress-related deterioration in performance of Japanese quail. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heat stress; vitamin E; zinc picolinate; quail